Relasi antara Tuhan dan Manusia Menurut Pandangan Ibrāhīm al-Kurānī - Frenky Mubarok (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2017)
This article describes the concepts of God and man’s relationship from a theological point of view along with Sufism. It focuses on Ibrāhīm al-Kurānī’s view on the issue. This article confirms that al-Kurānī attempts to reconcile the theological views of Ash‘ariyya and the divine worldviews of the Sufis, especially that of Ibn ‘Arabī’s philosophical Sufism. Al-Kurānī argues that there has been interconnectedness between common concepts expressed by the Sufis such as waḥdat al-wujūd and tajallī and the concept of al-kasb promulgated by Ash‘ariyya. The author finds that the concepts of ittiḥād and ḥulūl are not two mystical concepts that explain the relationship of God and man, rather these two concepts are a mere psychological condition sensed and experienced by the Sufis who try to enter the realm of ma‘rifa. Al-Kūrānī also argues that the relation between God and man can be explained through the concept of tajallī. He sees that this concept is compatible with Ash‘ariyya’s concept of al-kasb. Al-Kūrānī adds that causality is not an undoubtedly exact matter. It means that the causality does not discord against the notion of waḥdat al-wujūd.